2015
DOI: 10.1039/c4ra17314g
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable visible light-triggered cytotoxicity of mitochondria targeting mixed-ligand cobalt(iii) complexes of curcumin and phenanthroline bases binding to human serum albumin

Abstract: Co(iii) complexes of curcumin and phenanthroline bases show remarkable visible-light induced cytotoxicity in HeLa cells but are much less toxic in dark and to normal cells. The complexes bind to HSA with significant affinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 93 publications
1
47
0
2
Order By: Relevance
“…37 As shown in Figure 4, treating A549 cells with Cur and Cur-SLNs in the dark did not alter the cell cycle, compared with the untreated control group. In contrast, after they were exposed to the excitation light at 430 nm, A549 cells treated with Cur-SLNs showed 49.26% arrest in G2/M phase of cell cycle leading to cell death and the cells treated with Cur showed 25.29% arrest in G2/M phase.…”
Section: Cell Cycle Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…37 As shown in Figure 4, treating A549 cells with Cur and Cur-SLNs in the dark did not alter the cell cycle, compared with the untreated control group. In contrast, after they were exposed to the excitation light at 430 nm, A549 cells treated with Cur-SLNs showed 49.26% arrest in G2/M phase of cell cycle leading to cell death and the cells treated with Cur showed 25.29% arrest in G2/M phase.…”
Section: Cell Cycle Studiesmentioning
confidence: 97%
“…40 It is well known that Cur exposed to 430 nm light could generate a large amount of ROS, inducing the apoptosis of cancer cells. 32,37,41 Cytotoxic intracellular ROS can cause damage to mitochondria in cells, resulting in cell death. Our results demonstrated that SLN was a good drug delivery system for Cur, which enhanced its intracellular uptake and slowed down its hydrolysis in PDT.…”
Section: Discussionmentioning
confidence: 99%
“…The electronic absorption spectra of the complexes in aqueous DMF showed a common ligand-based band around 270 nm. In addition, complex 2 showed a strong curcumin-based π → π* visible absorption band within 400˗500 nm in 5% aqueous DMF [31]. were observed.…”
Section: A Medium Intensity Fe-o-fementioning
confidence: 92%
“…These values are considerably less than the spin-only value of 5.92 µ B /Fe suggesting antiferromagnetic interaction between the two iron(III) centres via the µ-oxo bridge [51]. The electrospray ionization mass spectrometry (ESI-MS) of the complexes in methanol displayed a single peak corresponding to [M˗2ClO 4 -] 2+ species [31]. The electronic absorption spectra of the complexes in aqueous DMF showed a common ligand-based band around 270 nm.…”
Section: A Medium Intensity Fe-o-fementioning
confidence: 96%
See 1 more Smart Citation